Neuraminidase and polymerase inhibitors in the treatment and prevention of influenza in children - Szwejkowska, Martyna; Nitsch-Osuch, Aneta (Family Medicine & Primary Care Review, 2025)
Despite the widespread availability of preventive vaccinations, influenza virus infections continue to affect millions of pediatric patients worldwide. This group constitutes a significant reservoir for further disease spread, which might lead to epidemics or pandemics. The article presents the use of neuraminidase and polymerase inhibitors in influenza prophylaxis and treatment, with a specific focus on the pediatric population. It is based on current recommendations, the latest scientific literature, and research findings. This work provides a recap of basic information regarding the structure and replication of the influenza virus in order to allow for a better understanding of the mechanism of action of individual drugs. The authors of the article focus on the proven efficacy and safety of registered medical preparations. The study involves a comparison of recommended influenza treatment options, and it presents both the advantages and limitations of each drug, which is crucial for selecting the most effective therapy in children. In the article, the significant role of influenza virus genetic variability is focused on, as it leads to the emergence of highly pathogenic variants and contributes to the spread of resistance in all drug classes. Continuous monitoring of the virus and the effectiveness of influenza antiviral drugs is essential for the ongoing development of new therapeutic options, particularly in the pediatric population.